2010
DOI: 10.1021/la104024t
|View full text |Cite
|
Sign up to set email alerts
|

Thorny Devil Nanotextured Fibers: The Way to Cooling Rates on the Order of 1 kW/cm2

Abstract: In the present work high-heat-flux surfaces, which should serve at temperatures of up to 200 °C, were covered by electrospun polymer nanofiber mats with thicknesses of about 30 μm. Then, four different metals were electroplated on separate polymer mats, namely, copper, silver, nickel, and gold. As a result, copper-plated nanofiber mats took on an appearance resembling that of a small Australian thorny devil lizard (i.e., they became very rough on the nanoscale) and acquired a high thermal diffusivity. Silver-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(51 citation statements)
references
References 23 publications
0
50
1
Order By: Relevance
“…[18] Electrospun nanofiber meshes or mats are used as templates for fabricating metal based conductive networks (see Table 1). [2,19,20] Conformal metal coating on a 3D structure requires homogeneous growth of a metal layer conforming to the topology of a substrate. Thus it forms topologically a metal network on top of polymer nanofibers, which is identified with a two-dimensional (2D) conductive network.…”
Section: Doi: 101002/aelm201900767mentioning
confidence: 99%
See 1 more Smart Citation
“…[18] Electrospun nanofiber meshes or mats are used as templates for fabricating metal based conductive networks (see Table 1). [2,19,20] Conformal metal coating on a 3D structure requires homogeneous growth of a metal layer conforming to the topology of a substrate. Thus it forms topologically a metal network on top of polymer nanofibers, which is identified with a two-dimensional (2D) conductive network.…”
Section: Doi: 101002/aelm201900767mentioning
confidence: 99%
“…For nylon and ePTFE nanofibers, the mean values of diameters are smaller than 100 nm. 2020, 6,1900767 Au nanotrough [19] One layer (2D) a) Electrospun PVA b) / PVP c) NFs d) Metal (Ni, Cu, Ag, Au)/polymer nanofiber mat [20] Top layer (2D) Electrospun PAN f) NFs The water wettability of the four kinds of nanofiber membranes are analyzed by water contact angles shown in Figure S1a-d, Supporting Information.…”
Section: Characterization Of Polymer Nanofiber Membranesmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Indeed, due to their high surface area to volume ratio, they are attractive in many biomedical applications such as scaffolds used in tissue engineering, drug release, artifi cial organs, wound healing and vascular grafts. [ 10,11 ] Due to the expanding demand for nanofi bers across a wide range of industries, there needs to be an improvement in the current state-ofart technologies to mass produce them more consistently, reliably, robustly and cost effectively.…”
Section: Introductionmentioning
confidence: 99%
“…13 Nonwovens are used not only to intercept impacting drops, but also to deliver them to a surface on which they are deposited as a coating, as in the recently introduced method of cooling high-heat-flux electronic devices and server rooms through electrospun nanofiber mats. 14 The latter work, as well as the accompanying works, [15][16][17][18] in fact, demonstrated that the concept of hydrophobic micro-and nano-textured filters and porous coatings might be intrinsically vulnerable, since it is based on a misconception of static hydrophobicity. For example, in ref.…”
Section: Introductionmentioning
confidence: 99%
“…23 On the other hand, drop impact onto nanofiber mats (both electrospun or not) revealed that under certain conditions they promote dynamic wettability rather than repelling water. [14][15][16][17][18]22,26 Moreover, it was recognized that due to the large disparity between the drop and the inter-fiber pore sizes (the drop diameter D of the order of 1 mm and the pore size d of the order of 1-10 mm), liquid accumulates the kinetic energy at the pore entrances and protrudes into them with a speed of the order of (D/d)V z 100 V where V is the impact velocity. This effect is reminiscent of the mechanism of formation of shaped-charge (Munroe) jets and is kindred to the widely known way of opening wine bottles by a sufficiently strong palm hit onto their bottom.…”
Section: Introductionmentioning
confidence: 99%